2008
DOI: 10.2116/analsci.24.355
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Chemical Species of Arsenic on Sensitivity in Graphite Furnace Atomic Absorption Spectrometry

Abstract: The sensitivity of graphite furnace atomic absorption spectrometry (GFAAS) to arsenobetaine (AB) was 1.3-times higher than to inorganic As. In order to understand the mechanism underlying this observation, the atomization processes for both chemical species were investigated in terms of the enthalpy change (ΔH) during the atomization process in GFAAS. The enthalpy change of AB was slightly lower than that of inorganic As, which suggested that AB was atomized more efficiently than was inorganic As. Moreover, it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Recently, it has been noted that arsenobetaine exhibits a 30% higher sensitivity than inorganic As, possibly due to its slightly lower enthalpy, which permits better atomization [177]. Moreover, this study also reported that several other organic species yield enhanced sensitivity over inorganic As [177], highlighting the necessity of further studies to improve the atomization process in order to increase efficiency and obtain similar sensitivities for all chemical species of the same element.…”
Section: Spectrometer Improvementssupporting
confidence: 50%
See 3 more Smart Citations
“…Recently, it has been noted that arsenobetaine exhibits a 30% higher sensitivity than inorganic As, possibly due to its slightly lower enthalpy, which permits better atomization [177]. Moreover, this study also reported that several other organic species yield enhanced sensitivity over inorganic As [177], highlighting the necessity of further studies to improve the atomization process in order to increase efficiency and obtain similar sensitivities for all chemical species of the same element.…”
Section: Spectrometer Improvementssupporting
confidence: 50%
“…Moreover, this study also reported that several other organic species yield enhanced sensitivity over inorganic As [177], highlighting the necessity of further studies to improve the atomization process in order to increase efficiency and obtain similar sensitivities for all chemical species of the same element.…”
Section: Spectrometer Improvementsmentioning
confidence: 60%
See 2 more Smart Citations
“…Published work is often difficult to examine from this perspective, as the data for the response of the instrument to standards of the different species are often not reported, nor is it clear whether concentrations are based on the mass of the species or of the element of interest. Narukawa et al 175 found that the ETAAS sensitivity of As was 1.3-times higher for arsenobetaine than for iAs, which they attributed to differences in the mechanisms of their atomization processes, suggesting that the two species are not converted to a common form during the ashing stage and further suggesting that a chemical modifier is needed.…”
Section: Detectionmentioning
confidence: 99%